Being There: Mindfulness as Ethical Classroom Practice - Paula Mathieu (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Incorporating mindfulness practices in teacher training for writing programs is supported by disciplinary scholarship in composition, spiritual writing, and research in neuroscience.